2020
DOI: 10.3389/fcomm.2020.510278
|View full text |Cite
|
Sign up to set email alerts
|

#T1DLooksLikeMe: Exploring Self-Disclosure, Social Support, and Type 1 Diabetes on Instagram

Abstract: Type 1 diabetes (T1D) is diagnosed mostly during childhood or adolescent years. During such transitional phases of life, having support from others in similar situations can reduce feelings of isolation and loneliness. Instagram, a platform with high use among teens or young adults, acts as an alternative to traditional online health communities. To better understand individuals self-disclosure on Instagram related to T1D, we conducted an exploratory quantitative content analysis of a sample of 423 posts using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 81 publications
(97 reference statements)
1
12
0
4
Order By: Relevance
“…Based on previous studies, the authors explain the above results as follows: the fact that individuals express their feelings, moods and thoughts to friend groups on SNSs makes individuals’ online relationships close and growing (Mohan Masaviru, 2016; Holtz and Kanthawala, 2020). As online relationships develop, individuals receive support (instrumental, informational and emotional) from virtual groups on SNSs (Trepte et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on previous studies, the authors explain the above results as follows: the fact that individuals express their feelings, moods and thoughts to friend groups on SNSs makes individuals’ online relationships close and growing (Mohan Masaviru, 2016; Holtz and Kanthawala, 2020). As online relationships develop, individuals receive support (instrumental, informational and emotional) from virtual groups on SNSs (Trepte et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to some researchers, individuals with high levels of online self-disclosure are often more interested in bridging, linking, maintaining social capital and online social support (Lee et al , 2013). Exposure to self-disclosure leading people to disclose each other, which further leads to the development of trust and relationships (Mohan Masaviru, 2016; Holtz and Kanthawala, 2020). Individuals can establish and maintain successful and supportive relationships only when they express their feelings and thoughts to the communicator (Trepte et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used a free, open-source data collection tool (Netlytic) to gather and code Instagram posts with the popular hashtag #t1dlookslikeme, finding that users were using this hashtag to self-disclose about Type I diabetes and gain social support (Holtz & Kanthawala, 2020). Another study found that diabetes-related TikTok videos in Chinese were primarily about disease management and created by three different types of users: health professionals, science communicators, or general users, suggesting that some professionals have begun to use this platform to spread chronic health information (Kong et al, 2021).…”
Section: Topical Reviewmentioning
confidence: 99%
“…The platform is especially favored among digital natives (Laestadius, 2017). A growing amount of users on this platform share their experiences and everyday life of living with T1D (Elnaggar et al, 2020;Holtz & Kanthawala, 2020;Ranjanala et al, 2022). T1D is an autoimmune disease with serious short-term and long-term implications, a significant impact on health care systems (Lancaster et al, 2010) and mostly diagnosed during childhood or adolescence (Atkinson et al, 2014).…”
Section: The Portrayal Of T1d On Instagrammentioning
confidence: 99%